BeckwithWiedemann Syndrome - Mohsin, Fauzia; Islam, Rubaiya; Begum, Tahmina; Azad, Kishwar; Nahar, Nazmun (Journal of Bangladesh College of Physicians and Surgeons, 2015)
BeckwithWiedemann syndrome (BWS) is a disorder of growth regulation characterized by macrosomia, macroglossia and developmental abnormalities with a predisposition to tumour development. The diagnosis of Beckwith-Wiedemann syndrome may be missed because of variable or incomplete clinical expression. Here we present a case of a newborn delivered at BIRDEM (Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders) General Hospital, presenting with macrosomia, macroglossia and hypoglycaemia. The baby also had umbilical hernia and asymmetry of limbs. The case is presented in order to create further awareness and to highlight the peculiarity of management of this rare disorder. J Bangladesh Coll Phys Surg 2014; 32: 167-170